2011
DOI: 10.1177/0883073811428009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hyperactivity/Inattention With Adiposity and Lifestyle Characteristics in Preschool Children

Abstract: We performed a cross-sectional study in 450 nonreferred preschool children aged 4 to 6 years to assess the association between hyperactivity/inattention with adiposity and lifestyle characteristics. Measurements included scores of hyperactivity/inattention, adiposity, objectively measured physical activity, television viewing, and eating habits. Higher scores of hyperactivity/inattention were associated with lower percentage body fat, higher levels of physical activity, and less time spent in sedentary activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 46 publications
6
43
0
Order By: Relevance
“…The finding that TV viewing was associated with the Hyperactive-Distractible factor is consistent with previous research that indicates a relationship between hyperactivity/inattention and higher levels of TV viewing (Ebenegger et al, 2012;Miller et al, 2007). Miller et al (2007) recruited 170 preschool children who were divided into a control group of children exhibiting three or fewer ADHD symptoms and an experimental group at-risk of developing ADHD who exhibited six or more hyperactive/inattentive symptoms as rated by parents and teachers.…”
Section: Behavioursupporting
confidence: 85%
“…The finding that TV viewing was associated with the Hyperactive-Distractible factor is consistent with previous research that indicates a relationship between hyperactivity/inattention and higher levels of TV viewing (Ebenegger et al, 2012;Miller et al, 2007). Miller et al (2007) recruited 170 preschool children who were divided into a control group of children exhibiting three or fewer ADHD symptoms and an experimental group at-risk of developing ADHD who exhibited six or more hyperactive/inattentive symptoms as rated by parents and teachers.…”
Section: Behavioursupporting
confidence: 85%
“…One of them showed a lower BMI in children with greater manifestation of ADHD symptoms (estimated with the use of the Conners' Hyperactivity Index -parent version) at the age of 56 months (Heinonen et al 2011). Results obtained by Ebenegger et al (2011) indicated that a high level of hyperactivity/ inattention was not associated with higher BMI and adiposity in preschool children. Another research with a separate analysis for preschool age (ranging from 2 to 5 years), showed no differences in the prevalence of overweight between children with ADHD and children in the general population .…”
Section: Discussionmentioning
confidence: 95%
“…Between 60 and 70% of children with a high level of ADHD symptoms do not have a friend in their class (Hoza et al 2005), and their social problems increase as they progress from childhood to adolescence (Hoza et al 2005;Cervantes et al 2013). Additionally, a study by Ebenegger et al (2011) showed that in spite of higher physical activity, preschool children with ADHD consume less healthy food or spend more time in front of the television. The beginning of school education (at 6-7 years of age, depending upon country of residence, and at 7 years of age in Poland for the examined cohort) also coincides with the onset of the critical phase for the development of self-esteem (Barber et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that effects may be most apparent in adulthood, rather than in childhood. However, we know of only three studies that reported results for samples limited to children under age 10; all controlled for medication effects and still found that ADHD or ADHD symptoms were associated with lower, not higher BMI (Ebenegger et al, 2012; Fliers et al, 2013; A. W. van Egmond-Fröhlich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%